Web-based language learning and speaking anxiety. Issue 5 (4th July 2022) - Bashori, Muzakki; van Hout, Roeland; Strik, Helmer; Cucchiarini, Catia
Abstract: Foreign Language Speaking Anxiety (FLSA) is known to negatively affect the performance of foreign language learners. Among the four language skills, speaking is the most anxiety-provoking skill. We investigated the presence of FLSA in Indonesian vocational high school students and we tested whether web-based language learning might help to reduce speaking anxiety, in particular when the facility in question is equipped with Automatic Speech Recognition (ASR). A mixed methods research was employed to investigate FLSA in 573 vocational high school students. A subset of them ( n = 167) was selected to participate in two ASR-based web-experiments using www.iloveindonesia.my.id and NovoLearning. We additionally interviewed 11 of the students who participated in these web-experiments and five English teachers. The results showed that students indicated a moderate-to-serious level of FLSA, that they evaluated the learning websites positively, and believed that web-based language learning could alleviate their speaking anxiety. The interviews revealed that students felt less anxious when speaking in front of the ASR-based websites compared to speaking to peers or people. In order to evaluate the real effectiveness of ASR-based learning websites, future studies should investigate actual improvement of learners' speaking skills over a longer period of time.